A Structural Model of Business Performance: An Empirical Study on Tobacco Farmers - Sony Heru Priyanto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
Few studies have been conducted on how farmers’ entrepreneurship affects their farm performance. However, factors of entrepreneurship have not been adequately explored by researchers. Textbooks and articles on farm management usually stress the importance of farmers’ management capability with respect to their farm output. Unfortunately, they have failed to relate management capability to entrepreneurship. This study was conducted using a multilevel analysis with Structural Equation Model (SEM) to know the causal relationships among environment factors such as the country’s economy, natural resources, institutions and organizations, individual backgrounds, entrepreneurship, management capacity, and farm performance. The cross-sectional data was obtained in 2003 from four dominant tobacco-producing districts in Central Java. The multilevel model –that relates external environment, entrepreneurship, and management capacity– can adequately represent the data to estimate farm performance.The results of the analysis indicate that factors like personal aspects, together with physical, economic and institutional environments, affect farmers’ entrepreneurship. Personal aspects turn out to be the dominant factor that determines entrepreneurship and farm performance. This study also shows that farmers’ entrepreneurship is affected by their management capacity, which, in turn, affects the farmers’ farm performance. While there is no doubt in the adequacy of the model to estimate farm performance, this finding invites further investigation to validate it in other fields and scale of business, such as in small and medium enterprises and other companies. Furthermore, in order to evaluate the goodness of fit of the model in various contexts, further research both in a cross-cultural context and cross-national contexts using this model should be conducted.